Trustworthy 100-year digital objects Evidence after every witness is dead. - Gladney, Henry M. (ACM transactions on information systems.)
In ancient times, wax seals impressed with signet rings were affixed to documents as evidence of their authenticity. A digital counterpart is a message authentication code fixed firmly to each important document. If a digital object is sealed together with its own audit trail, each user can examine this evidence to decide whether to trust the content---no matter how distant this user is in time, space, and social affiliation from the document's source.We propose an architecture and design that accomplish this: encapsulation of digital object content with metadata describing its origins, cryptographic sealing, webs of trust for public keys rooted in a forest of respected institutions, and a certain way of managing information identifiers. These means will satisfy emerging needs in civilian and military record management, including medical patient records, regulatory records for aircraft and pharmaceuticals, business records for financial audit, legislative and legal briefs, and scholarly works.This is true for any kind of digital object, independent of its purposes and of most data type and representation details, and provides every kind of user---information authors and editors, librarians and collection managers, and information consumers---with autonomy for implied tasks. Our prototype will conform to applicable standards, will be interoperable over most computing bases, and will be compatible with existing digital library software.The proposed architecture integrates software that is mostly available and widely accepted.